Prenatal diagnosis and management of vasa previa in twin pregnancies: a case series and systematic review - Jauniaux, Eric; Melcer, Yaakov; Maymon, Ron (American journal of obstetrics and gynecology, 2017)
Twin pregnancies are at higher risks of velamentous cord insertion and vasa previa. In vitro fertilization is an additional risk factor of abnormal cord insertion and thus the incidence of vasa previa is likely to increase over the next decades. We sought to evaluate the role of ultrasound imaging in optimizing the management of twins diagnosed with vasa previa antenatally. We searched our database for twin pregnancies diagnosed with vasa previa and managed antenatally using measurements of cervical length and performed a systematic review of articles that correlated prenatal diagnosis of vasa previa in twins and pregnancy outcome. PubMed and MEDLINE were searched for studies published from 1987 through October 20, 2016, using specific medical subject heading terms, key words, and their combination. The primary eligibility criteria were articles that correlated prenatal ultrasound imaging of vasa previa and pregnancy outcome in twins. The secondary eligibility criteria was the use of cervical length in the management of twin pregnancies diagnosed antenatally with vasa previa. Two authors independently assessed inclusion criteria, data extraction, and analysis. The final selection included 3 case report series, 9 retrospective cohort studies, and 1 retrospective case-control study of vasa previa diagnosed prenatally and confirmed at birth in twin pregnancies. The search of our databases identified 6 cases of dichorionic-diamniotic twins and 1 case of monochorionic-diamniotic twins diagnosed prenatally with vasa previa between 22-29 weeks and managed using cervical length. Two cases were delivered by emergency because of rapid changes in cervical length in one and bleeding on placenta previa in the other at 33 and 30 weeks, respectively. The systematic review identified data on 56 cases. The incidence of twin pregnancies diagnosed antenatally with vasa previa in the cohort and case-control studies was 11.0%. Data on chorionicity were available in only 34 cases and cervical length measurements were used by only the authors of 2 case reports and 4 cohort studies. Velamentous cord insertion was the most common additional ultrasound findings in twins presenting with vasa previa in both our series and the systematic review. Vasa previa is associated with specific prenatal and obstetric complications with different outcomes in singletons compared to twins. Data on the diagnosis and management of vasa previa in twin pregnancies are limited but there is enough evidence to warrant guidelines for targeted screening. To enable the development of efficient management protocols tailored to the need of individual cases, future studies of the screening, diagnosis, and management of vasa previa should be prospective and multicentric with detailed data on twins including chorionicity and use of cervical length.